PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENDEKATAN TEACHING AT THE RIGHT LEVEL PADA SISWA KELAS V-B SDN 22 PALU - rezky Pratama Astiana; rizal rizal; okta okta (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This classroom action research served as a strategic initiative to elevate students’ mathematics achievement by applying the Teaching at the Right Level (TaRL) approach. The research was conducted with 28 fifth-grade learners from class V-B at SD Negeri 22 Palu, comprising 16 male and 12 female students. Data collection involved a combination of classroom observations and assessments of learning outcomes. The results demonstrated a steady and positive trajectory in student achievement from the initial (pre-action) stage through to the second cycle. In the early phase, 18 students met the minimum competency standards. This figure rose to 20 students during the first cycle, and further increased to 23 students in the second. These findings highlight the effectiveness of the TaRL approach in aligning instruction with learners' actual proficiency levels, thereby significantly enhancing mathematics learning outcomes among fifth-grade students at SD Negeri 22 Palu.